The effect of vitamin D supplementation on periodontal health: a systematic review and meta-analysis - Aafreen Gillani Haji; Benedetta Ghezzi; Sara Tagliaferri; Nagihan Bostanci; Elena Calciolari (Evidence-Based Dentistry, 2026)
Abstract Aims/objectives This systematic review aimed to assess whether supplementation with vitamin D compared to no supplementation or placebo might provide a significant benefit for periodontal and peri-implant health in terms of changes in probing pocket depth (PPD), clinical attachment level (CAL), tooth loss and implant loss. Methods Three databases were searched to identify randomized controlled trials (RCTs) and controlled clinical trials (CCTs) looking at the effect of vitamin supplementation on periodontal and peri-implant health with a minimum follow-up of 1 month. Meta-analysis of the weighted mean differences (MD), with 95% confidence intervals (CI) was performed when ≥3 studies with the same characteristics and follow-up were identified. Results Fourteen articles (13 RCTs and 1 CCT) were included for qualitative assessment, but none assessed the impact of vitamin D on peri-implant health. Three studies assessing the impact of vitamin D supplementation to non-surgical periodontal therapy with a total of four subset of subjects were included in the meta-analysis on changes in PPD with an estimated mean difference of 0.0023 mm (95% CI: −0.0378 mm to 0.0424 mm), which was not statistically significant ( p = 0.9110). Discussion Vitamin D supplementation does not confer a statistically significant additional benefit to non-surgical periodontal therapy in reducing probing pocket depth. Although vitamin D may exert anti-inflammatory effects on gingival tissues, current evidence is limited, heterogeneous, and insufficient to support a clear clinical recommendation. No studies addressing peri-implant health outcomes were identified, underscoring a gap in the literature. Well-designed, long-term randomized controlled trials that control for confounding variables are needed to determine the role of vitamin D supplementation in periodontal health.